2014
DOI: 10.1016/j.vaccine.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus vaccination under the exogenous boosting hypothesis: Two ethical perspectives

Abstract: Abstract:The varicella-zoster virus (VZV) causes two diseases: varicella ('chickenpox') and herpes zoster ('shingles'). VZV vaccination of children reduces exposure to chickenpox in the population and it has been hypothesized that this could increase the prevalence of shingles. This 'exogenous boosting' effect of VZV raises an important equity concern: introducing a vaccination program could advance the health of one population group (children) at the expense of another (adults and elderly). We discuss the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The authors concluded that better understanding of the processes is therefore needed [114]. If routine infant varicella vaccination causes an albeit small increase in the incidence of HZ, there is a potential ethical dilemma whereby varicella vaccination although protecting one population (children) might have a deleterious effect on older individuals [39]. Other workers have proposed a more pragmatic approach in which zoster vaccination is used to supplement the varicella program and prevent HZ in older adults [40,41].…”
Section: Evidence For Varicella Vaccinationmentioning
confidence: 99%
“…The authors concluded that better understanding of the processes is therefore needed [114]. If routine infant varicella vaccination causes an albeit small increase in the incidence of HZ, there is a potential ethical dilemma whereby varicella vaccination although protecting one population (children) might have a deleterious effect on older individuals [39]. Other workers have proposed a more pragmatic approach in which zoster vaccination is used to supplement the varicella program and prevent HZ in older adults [40,41].…”
Section: Evidence For Varicella Vaccinationmentioning
confidence: 99%
“…Following naturally acquired VZV infection, VZV-specific antibody and CMI responses continue to be re-boosted not only by reactivation of latent virus, but also exogenous re-exposure to VZV. Without the occasional exogenous VZV re-exposure, VZV-specific immune responses decline and VZV reactivation could lead to clinical manifestations of HZ [Hope-Simpson, 1965; Luyten et al 2014]. Although more evidence is needed to support the exogenous-boosting hypothesis [Ogunjimi et al 2013], future studies on its long-term effect on HZ incidence may shed more light.…”
Section: Discussionmentioning
confidence: 99%
“…Appeals to the well-being of society as a whole have also been made in arguments against recommending routine childhood varicella vaccine. For example, Luyten et al (2014) argue that one cannot justify universal childhood varicella vaccination, from the point of view of aggregate well-being, due to the significant short-term losses in QALYs (associated with the loss of exogenous boosting) that such a program would cause. These kinds of arguments are cited as a primary motivation for decisions by many European countries not to recommend routine childhood varicella vaccination (Gaillat et al 2011).…”
Section: One Virus Two Diseases Several Vaccines and Some Problemamentioning
confidence: 99%